The Role of Integration of Sports and Medicine, Training Processes, and Physical Fitness in Athlete Performance and Athlete Sports Success - Xu Zhang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The success of an athlete is contingent upon their performance, which can be optimally attained through the efficient integration of sports medicine, training, and physical conditioning. This particular element necessitates the focus of researchers, and the current study examines the impact of incorporating sports and medicine, the training regimen, and physical fitness on the athletic performance of individuals within China's sports complex. The researchers additionally investigate the role of athlete performance as a mediator in the relationship between the integration of sports and medicine, the training process, physical fitness, and the success of Chinese athletes in sports. Primary data was collected from athletes in a sports complex in China through the use of questionnaires. The data collected during this study was also analysed using SPSS-AMOS. The findings of the study indicate a significant association between the amalgamation of sports and medicine, the training modality employed, and physical fitness levels with the athletic performance observed within China's sports complex. The findings also indicate that the performance of athletes significantly mediates the association between the integration of sports and medicine, the training process, physical fitness, and the success of Chinese athletes in sports. The available research provides valuable insights for policymakers in developing policies aimed at enhancing the athletic performance of athletes by incorporating elements of sports medicine, training methodologies, and physical fitness.